Women Empowerment through Entrepreneurship in Violent-conflict Settings: Challenges and Opportunities - Rohaya, Mohd Nor; Ashemi, Baba Ali (Human Resource Management Academic Research Society, 2022)
Empowering women through entrepreneurship in violent-conflict contexts not only improves socioeconomic welfare of women but also help in restoring peace and social inclusion in society. This paper aims at exploring the challenges and opportunities facing women empowerment through entrepreneurship in violent-conflict contexts. A qualitative research approach is employed for achieving the objective of the study. Data for the study were collected through an in-depth semi-structured interview and participant observation. A total number of twenty-three (23) participants were purposely selected from five different communities affected by Boko Haram insurgency in Northeast Nigeria. The major findings of the study revealed that the challenges facing women an entrepreneur in a violent-conflict context is multifaceted and efforts to curtail these challenges also require a comprehensive and all-inclusive approach. The study further revealed that apart from the numerous challenges, violent-conflict environment also presents wide range of opportunities for exploitation. The study recommends that a more gender-sensitive entrepreneurship program is needed to achieve a sustainable peace in violent-conflict settings. Also, the need for adequate orientation for targeted beneficiaries towards achieving purposeful women empowerment programs.